Digital Workflow Accuracy in Prosthodontics: Comparison of Intraoral and Conventional Impression Techniques - ugli, Jumayev Asliddin Abdusamad; Astanovich, Akhmedov Alisher (American Journal of Biomedicine and Pharmacy, 2026)
The accuracy of prosthodontic restorations relies heavily on precise impressions, as discrepancies may lead to poor marginal fit, occlusal errors, and compromised long-term clinical outcomes. The introduction of digital workflows, including intraoral scanning, has revolutionized prosthodontics by offering potential improvements in accuracy, efficiency, and patient comfort compared to conventional impression techniques such as polyvinyl siloxane or polyether impressions. This article evaluates the comparative accuracy of intraoral digital impressions and conventional analog techniques, examining linear and volumetric deviations, marginal adaptation, prosthesis fit, and clinical feasibility. Clinical studies and laboratory evaluations are analyzed to assess the influence of material properties, scanning protocols, operator experience, and software algorithms on the precision of digital impressions. Evidence demonstrates that intraoral scanning offers comparable or superior trueness and reproducibility in single-unit and short-span restorations, while conventional impressions maintain advantages in edentulous or complex full-arch cases. Proper material selection, scanning strategy, and post-processing protocols are critical to maximize digital workflow accuracy and achieve predictable prosthodontic outcomes.